The Prevalence of Goitre in School Children in Sulaimani City - Mahwi, Taha Othman (Sulaimani Journal for Pure and Applied Sciences, 2005)
The Survey was done on school children in Sulaimani center by randomly selecting schools and students to represent the whole school children population in different areas. The study showed That the total number of school children that had been surveyed were 1427 students, Male: 632,Female 795 and the prevalence of goiter in female was: 59.24% (471 students) the prevalence of goiter in male was: 48.1%(304 students) and the overall prevalence of goiter was: 54.3%(775 students).
Keywords: Goiter; Iodine deficiency disorers; School children